Business relocations in the Netherlands: Why do firms move, and where do they go? - Kristin Kronenberg (European Regional Science Association (ERSA), 2011)
This study analyzes determinants of business relocation and identifies regional characteristics which attract relocating firms, using register data provided by Statistics Netherlands. Results indicate that the relocation decisions of firms are not only influenced by firm- and location-specific characteristics, but also by the qualities of a firm's workforce, and by the attractiveness of a municipality for individuals regarding the amenities which are provided. Furthermore, the findings show that relocation decisions are sector-dependent. Generally, its age and being located in an appealing municipality with high sectoral specialization keep a firm from relocating, whereas firms employing large shares of highly educated workers, paying high average salaries and being located in a municipality with high sector-specific wages are pushed out of their present location. Relocating firms avoid specialized municipalities, while they are attracted by densely populated, appealing municipalities with high wage levels (both general and sector-specific) and large shares of highly educated workers, and which are specialized in the firm's own sector.
Keywords: 330